Structure similarity and lattice dynamics of InSe and In₄Se₃ crystals - Bercha, D.M.; Rushchanskii, K.Z.; Kharkhalis, L.Yu.; Sznajder, M. (Condensed Matter Physics, 2000)
In the work it was shown that the In₄Se₃ crystal is similar by its dynamical properties to the InSe modulated crystal. The transformation of the D⁴₆h symmetry group of β-InSe crystal to D⁹₂h group of the In₄Se₃ structure and the D¹²₂h group of In₄Se₃ structure has been investigated. In spite of structure corrugation of In₄Se₃ layer, it is shown that the region of the weak bond in this crystal by the dynamical characteristics is similar to the weak bond region in InSe crystal. У роботі показано, що кристал In₄Se₃ за своїми динамічними властивостями близький до модульованого кристалу InSe. Досліджено перетворення групи симетрії D⁴₆h кристалу β-InSe до групи D⁹₂h структури In₄Se₄ і до групи D¹²₂h In₄Se₃. Показано, що незважаючи на гофрованість структури шару In₄Se₃, область слабкого зв’язку у ньому за динамічними властивостями є подібною до області слабкого зв’язку у кристалі InSe.